Levels of evidence in plastic surgery—bibliometric trends and comparison with five other surgical specialties - Agha, R; Devesa, M; Whitehurst, K; Fowler, A; Coe, R; Wellstead, G; Orgill, D; McCulloch, P (Springer Nature, 2016)
Background: Categorising research by level of evidence (LOE) is an important evidence-based medicine initiative. Our objective was to assess the change in LOEs in plastic surgery from 2003 to 2013 and compared this with five other surgical specialties. Methods: A search for all research articles published in the top three general plastic surgery journals (ranked by impact factor) was conducted for 2003 and 2013. Articles were then labelled as LOE 1–5 and compared to other specialties. Results: Mean LOE for plastic surgery improved by 4.1Â % from 3.86 (95Â % confidence interval 3.81–3.91) to 3.70 (95Â % confidence interval 3.64–3.74) from 2003 to 2013 respectively. All six surgical specialties improved their mean LOE (range 3.7 to 10.9Â %). By mean LOE, plastic surgery continues to rank five out of six. Conclusions: Plastic surgery is tending towards higher levels of evidence at a slow pace. The specialty must continue to drive towards higher levels of evidence. Level of Evidence: Not ratable.